2020
DOI: 10.3390/molecules25102382
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Chemical Profiling, Isolation and Evaluation of the Cytotoxic Potential of the Diterpenoid Siderol from Cultivated Sideritis euboea Heldr.

Abstract: Diterpenes are characteristic compounds from the genus Sideritis L., possessing an array of biological activities. Siderol is the main constituent of the ent-kaurene diterpenes in Sideritis species. In order to isolate the specific compound and evaluate for the first time its cytotoxic activity, we explored the dichloromethane extract of cultivated Sideritis euboea Heldr. To track the specific natural bioactive agent, we applied NMR spectroscopy to the crude plant extract, since NMR can serve as a powerful and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, compounds 28 and 29 correspond to fatty acid derivatives and their bioactivity has not been explored up to date. It is noteworthy that compound 29 has been recently isolated from S. euboea [49] and it was not identified in other Sideritis species, previously. Gathering all the above data, the present investigation reveals the presence of compounds 2 – 4 , 7 – 10 , 13 , 14 , 22 , 24 – 29 for the first time in S. cypria .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, compounds 28 and 29 correspond to fatty acid derivatives and their bioactivity has not been explored up to date. It is noteworthy that compound 29 has been recently isolated from S. euboea [49] and it was not identified in other Sideritis species, previously. Gathering all the above data, the present investigation reveals the presence of compounds 2 – 4 , 7 – 10 , 13 , 14 , 22 , 24 – 29 for the first time in S. cypria .…”
Section: Resultsmentioning
confidence: 87%
“…It is interesting that compound 7 was isolated from several Sideritis species, but not from S. cypria [45] . Moreover, compounds 8 and 9 are two very common phytosterols in genus Sideritis , [46–49] exerting numerous pharmacological activities [50–52] . It is intriguing to point out that compounds 5 – 9 were isolated from a polar extract, though they are generally characterized as mainly non‐polar secondary specialized products.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 – 3 were isolated from the non-polar fractions of the plant residue. This study represents the first report of triolein in genus Sideritis , whereas compounds 2 and 3 were extensively found in this genus and might also be characteristic compounds for the specific species [ 4 , 9 , 41 ]. Furthermore, the three isolated iridoids (compounds 4 – 6 ) were previously reported on genus Sideritis [ 8 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, its infusion (known as mountain tea) is widely consumed against mild gastrointestinal discomfort and common flu [ 5 , 6 , 7 , 8 ]. Previous studies reported the rich chemical profile of its extracts, including various metabolites with significant pharmacological effects [ 4 , 5 , 6 , 7 , 8 , 9 ]. The constantly increasing demand for mountain tea results in serious concerns about the survival of the wild Sideritis populations due to their overharvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the infusion of Sideritis syriaca was reported to inhibit HT-29 cell growth with value of ~ 60% at 1.00 µg/µL concentration after 48 h by Kogiannou et al (2013). The IC50 value of siderol, a well-known major constituent of the genus Sideritis, was calculated as 26.4±3.7 µM in DLD-1 cell line (Tomou et al, 2020). The hexane extract of Ferula hermonis root (IC50: 25 µg/mL) was found to have moderate sensitivity on the LoVo cell line (Abutaha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%